Unmet expectations and job involvement among doctors: does individual conscientiousness play a mitigating role?. Issue 12 (2nd December 2022) - Koomson, Samuel; Mensah, Abigail Opoku; Koomson, Eric
Abstract : Background/Aims: Doctors are responsible for leading the care of patients. This study analysed the moderating role of individual conscientiousness on the relationship between psychological contract breach and levels of job involvement among medical doctors working in Ghana. A psychological contract breach occurs when an organisation does not deliver on their expected obligations to an employee, whether these expectations are written or unwritten. Methods: All 251 doctors working in the upper east and upper west regions of Ghana were invited to participate, of which 214 doctors responded. Participants completed self-administered questionnaires, with 15 statements relating to psychological contract breach, 10 statements relating to job involvement and four statements relating to individual conscientiousness. Respondents rated their agreement to the statements on a 7-point Likert scale (1=least agreement; 7=strongest agreement). Participant demographics were also collected. Relationships between the data for each section were analysed using the Statistical Package for the Social Sciences (version 24) and the Smart PLS 2.0M.3. Results: Psychological contract breach was found to have a significant negative relationship with job involvement ( P <0.05). Conscientiousness had a moderating effect on this relationship, meaning that doctors who were more conscientious were less likely to reduce their job involvement when a psychological contract breach occurred. Conclusions: When a psychological contract breach occurs, doctors who have a conscientious personality trait are likely to continue showing high levels of job involvement. This implies that doctors who are naturally hardworking, organised, disciplined and highly motivated are more likely to persevere with psychological and emotional commitment to their role, but this may make them more vulnerable to mistreatment (whether intentional or not) by their employer.